The WSES: what do we see in the future? - De Simone, Belinda (World J Emerg Surg, 2021)
We present the New Year letter from the WSES board to wish everyone a new year full of positive surprises and good news, despite COVID-19 pandemic. We confirm the WSES primary aim: to promote education in emergency surgery putting together all the world experts on emergency surgery without restrictions or boundaries, in inclusivity, equality, and equal opportunities. This will be the year of innovations and WSES will assess the application of artificial intelligence technologies in emergency and trauma surgery. Thank you All for trusting us with your collaboration.